2022
DOI: 10.1021/acschembio.2c00393
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Phosphorylation-Induced Protein Allostery and Conformational Dynamics of Glycogen Phosphorylase via Integrative Structural Mass Spectrometry and In Silico Modeling

Abstract: Allosteric regulation plays a fundamental role in innumerable biological processes. Understanding its dynamic mechanism and impact at the molecular level is of great importance in disease diagnosis and drug discovery. Glycogen phosphorylase (GP) is a phosphoprotein responding to allosteric regulation and has significant biological importance to glycogen metabolism. Although the atomic structures of GP have been previously solved, the conformational dynamics of GP related to allostery regulation remain largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 55 publications
5
10
0
Order By: Relevance
“…A notable HDX uptake difference of 1.7 Da was identified in the peptide containing residues Arg309 and Arg310, which play a crucial role in the G6P allosteric site interactions, as shown in the crystallographic model of the binding epitope, Figure3. Despite this, the results showed that the stability of the α8 helix (residues 307−326) remained unchanged within the conventional measurement time frame, in agreement with prior studies 21. This suggests that part of the binding epitope for G6P, as determined by crystallography, is not captured in HDX-MS data when measured within the standard time window (i.e., > 10 s).These findings suggest that the N-terminus of the α8 helix and the preceding 280s loop are highly sensitive to allosteric modulation and that the Arg309 and Arg310 residues play a crucial role in these structural changes.This may represent direct mediation of allostery from the nucleotide site via the rigid α8 helix to the active site, although it is unclear how the partial release of the 280s entropic gate can manifest as inhibitory.…”
supporting
confidence: 89%
“…A notable HDX uptake difference of 1.7 Da was identified in the peptide containing residues Arg309 and Arg310, which play a crucial role in the G6P allosteric site interactions, as shown in the crystallographic model of the binding epitope, Figure3. Despite this, the results showed that the stability of the α8 helix (residues 307−326) remained unchanged within the conventional measurement time frame, in agreement with prior studies 21. This suggests that part of the binding epitope for G6P, as determined by crystallography, is not captured in HDX-MS data when measured within the standard time window (i.e., > 10 s).These findings suggest that the N-terminus of the α8 helix and the preceding 280s loop are highly sensitive to allosteric modulation and that the Arg309 and Arg310 residues play a crucial role in these structural changes.This may represent direct mediation of allostery from the nucleotide site via the rigid α8 helix to the active site, although it is unclear how the partial release of the 280s entropic gate can manifest as inhibitory.…”
supporting
confidence: 89%
“…To further estimate the advances achieved with the ms2min system, we compared the information content available from the conventional (≥seconds) and the millisecond time range (Figure D) (the gray shaded region denotes the conventionally acquired time window data). Data from the ms2min in the 1–300 s time domain were similar to published values from CTC-PAL experiments (given limitations in the interpretation from variation in the labeling conditions and LC–MS systems) . We found certain regions in this large enzyme that have little to no information content by HDX-MS when resolved at the seconds-minutes time window, but almost complete kinetics were obtained when the HDX window was extended by 3 orders of magnitude, down to 50 ms.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the ms2min in the 1−300 s time domain were similar to published values from CTC-PAL experiments (given limitations in the interpretation from variation in the labeling conditions and LC−MS systems). 54 We found certain regions in this large enzyme that have little to no information content by HDX-MS when resolved at the seconds-minutes time window, but almost complete kinetics were obtained when the HDX window was extended by 3 orders of magnitude, down to 50 ms. Insights into the structural changes upon Ser14 phosphorylation were attained, though it is evident that expansion of the time window stands to detect structural perturbations more sensitively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The sample may then undergo mild fragmentation by either an ECD or ETD to cleave labile interdomain bonds, providing additional ‘domain’ level resolution [ 54–56 ]. While top-down experiments will not provide local resolution of mass shifts, the technique is utilized to compare global deuterium incorporation rates and observe interspecies differences that may occur, such as the influence of post-translational modifications, as well as it will aid in characterizing conformationally heterogenous samples [ 57–59 ].…”
Section: Hdx-ms Experiments Designmentioning
confidence: 99%